Antifungal Effect of Henna against Candida albicans Adhered to Acrylic Resin as a Possible Method for Prevention of Denture Stomatitis - Nawasrah, Amal (Int J Environ Res Public Health, 2016)
Denture stomatitis is a very common disease affecting the oral mucosa of denture wearers. The aim of this study was to measure the antifungal effect of henna against Candida albicans adhered to acrylic resin as a possible method for prevention of denture stomatitis. One-hundred-eighty acrylic plates were prepared of heat-cured acrylic denture resin. The specimens were divided into six groups of 30 samples each. The first group was only polymer and monomer following the conventional manufacturer instruction for processing complete dentures. The other five groups were processed by adding different concentration of Yamani henna powder (Harazi) to the polymer in a concentration of henna: polymer 1%, 2.5%, 5%, 7.5% and 10%, respectively. Samples were incubated in artificial saliva rich with Candida albicans at 37 °C, and the effect of henna on Candida albicans was evaluated in two different methods: semi-quantitative slide count and a culture-based quantitative assay (quantitative). Variation in the number of live Candida was observed with the increase in the concentration of Yamani henna powder. It was observed that the variation in live Candida, between control group and group B (concentration of Yamani henna powder was 1%), was statistically significant with a p-value of 0.0001. Similarly, variations in live Candida were significant, when the concentration of powder was 7.5% or 10% in contrast with control group and p-values were 0.0001 and 0.001 respectively. Adding henna to acrylic resin denture could be effective in controlling Candida albicans proliferation on the denture surface; however, its effects on the physical properties of acrylic resin denture need further studies.